Influence of mindmapping on attitude and achievement in history of Secondary Two (Normal) course pupils - Shan Mugam Sidambaram. (2008)
Studies have showed that History has always been a challenging subject for students with low academic ability. This quasi-experimental study was designed to investigate the influence of Mind mapping on History achievement and attitude towards History among student in Secondary Two Normal (Academic) course.